2019
DOI: 10.1111/jfd.13084
|View full text |Cite
|
Sign up to set email alerts
|

Review of infectious agent occurrence in wild salmonids in British Columbia, Canada

Abstract: Wild Pacific salmonids (WPS) are economically and culturally important to the Pacific North region. Most recently, some populations of WPS have been in decline. Of hypothesized factors contributing to the decline, infectious agents have been postulated to increase the risk of mortality in Pacific salmon. We present a literature review of both published journal and unpublished data to describe the distribution of infectious agents reported in wild Pacific salmonid populations in British Columbia (BC), Canada. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 142 publications
1
11
0
Order By: Relevance
“…About half of these farms may be active in any given year (http://www.dfo-mpo.gc.ca/aquaculture/bc-aquaculture-cb-eng.html). Although many infectious agents are naturally occurring in British Columbia salmonids (Jia et al 2020), Atlantic Salmon farms have been identified as a potential contributor to the decline of Fraser River salmonid stocks through increased transfer of sea lice, bacteria, and viruses (Price et al 2010; Kent 2011; Godwin et al 2017). Short time series, however, have limited the statistical power to detect relationships between salmonid survival and pathogen or parasite variables (Connors 2011; Korman 2011).…”
Section: Figurementioning
confidence: 99%
“…About half of these farms may be active in any given year (http://www.dfo-mpo.gc.ca/aquaculture/bc-aquaculture-cb-eng.html). Although many infectious agents are naturally occurring in British Columbia salmonids (Jia et al 2020), Atlantic Salmon farms have been identified as a potential contributor to the decline of Fraser River salmonid stocks through increased transfer of sea lice, bacteria, and viruses (Price et al 2010; Kent 2011; Godwin et al 2017). Short time series, however, have limited the statistical power to detect relationships between salmonid survival and pathogen or parasite variables (Connors 2011; Korman 2011).…”
Section: Figurementioning
confidence: 99%
“…Gill copepod number was assessed as a predictor of survival because of its potential association with overall parasite load and immune system function. However, it is understood that that parasite load results from a complex interaction of factors such as exposure and immune response and that other pathogens are likely present that could influence survival in adult salmonids (Jia et al 2020).…”
mentioning
confidence: 56%
“…However, it is understood that that parasite load results from a complex interaction of factors such as exposure and immune response and that other pathogens are likely present that could influence survival in adult salmonids (Jia et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, piscine orthoreovirus appears to be widespread in both diseased and nondiseased farmed and wild salmon, especially in species indigenous to the Pacific Northwest. 11 Given the inability to culture piscine orthoreovirus in fish cell lines, the primary means for identifying the virus involve molecular diagnostic tests. However, because no causal link between the virus and disease or death has been proven, it is not clear how to interpret a positive molecular diagnostic test result, especially for salmon that appear to be healthy, or how to interpret a negative molecular diagnostic test result in salmon with heart and skeletal muscle inflammation or erythrocytic inclusion body syndrome.…”
Section: Aquaculture: Unclear Disease Etiologymentioning
confidence: 99%